PRINTED HERITAGE COLLECTIONS OF THE REFORM MOVEMENT SĄJŪDIS IN LITHUANIA - JANKAUSKAITĖ, VAIDA (Knygotyra, 2012)
During the Soviet occupation, the Lithuanian reform movement Sąjūdis encouraged the development of the uncensored press and influenced the end of the Soviet government-controlled press system. Sąjūdis published and widely disseminated illegal periodicals and onetime publications, which concentrated the Lithuanian society for the reconstruction of Lithuania’s independence in 1990. Currently, there is no research of the Sąjūdis printed heritage.The object of the present study is the Sąjūdis press of the early period (published from 13 June 1988 till 11 March 1990) purposely stored in Lithuania’s memory institutions and private collections. The aim of this study was to establish the best known and available collections.Every Sąjūdis publication became particular and nowadays needs an appropriate view and preservation in special heritage departments of the Lithuanian memory institutions. Their first tasks would be to prepare a thorough bibliography and to validate the value of these heritage collections, which have unique inscriptions and ownership marks sometimes made by famous people.The collections were investigated in three archives, eleven libraries, nine museums and two personal collections. There is no complete surviving Sąjūdis printed heritage collection. During the Sąjūdis press distribution (1988–1990), the Lithuanian libraries, museums and persons collected it actively, and later the formation of this heritage was spontaneous. The most common ways of acquisition were the national legal deposit, donations, purchase, and interchange. The dominant donors of the Sąjūdis printed heritage were the staff, members of Sąjūdis, historians, journalists and other persons who realized the necessity of keeping this heritage. The largest collection, according to the title number, belongs to the private collector (bibliophile) Žilvinas Januška. Personal collections, because of their methodical and purposeful retrospective formation, have more titles than the institutional ones. The biggest collection according to the number of copies belongs to the Vilnius University Library. However, there are 10 per cent of unidentified and lost titles of the Sąjūdis printed heritage. There is a possibility to find more of them in Lithuania.Sąjūdis press contains materials of different periods, this fact endangers this heritage to disappear if not conserving it. This heritage is in good condition in Lithuanian museums and in worse condition in the archives, especially in libraries.In conclusion, Lithuanian memory institutions have to fulfil their mission and to preserve the printed heritage of Sąjūdis better.
Keywords: ...